The lncRNA HOTAIR attenuates pyroptosis of diabetic cardiomyocytes by recruiting FUS to regulate SIRT3 expression - Jing Xiong; Qing Zhou (Kaohsiung Journal of Medical Sciences, 2023)
Abstract Diabetic cardiomyopathy (DCM) is a serious cardiovascular complication of diabetes that severely affects the quality of life of diabetic patients. Long noncoding RNAs (lncRNAs) play important roles in the pathogenesis of DCM. However, the role of the lncRNA homeobox transcript antisense RNA (HOTAIR) in the progression of DCM remains unclear. The present study aimed to investigate the role of HOTAIR in high glucose (HG)‐induced pyroptosis in cardiomyocytes. The expression of the lncRNA HOTAIR, FUS, and SIRT3 in H9C2 cardiomyocytes was detected by RT–qPCR. Western blotting was used to evaluate the expression of FUS and SIRT3 as well as that of pyroptosis‐ and inflammation‐related proteins. RT–qPCR and ELISA were used to determine the expression and secretion of IL‐1β and IL‐18. RNA pulldown and RIP experiments were used to validate the binding relationship among HOTAIR, FUS, and SIRT3. Flow cytometry was performed to detect pyroptosis. HG induced pyroptosis and elevated the expression of proteins associated with pyroptosis and inflammation (NLRP3, GSDMD‐N, cleaved caspase‐1, IL‐1β, and IL‐18) in cardiomyocytes. HOTAIR and SIRT3 levels were decreased in HG‐exposed H9C2 cells. Additionally, overexpression of HOTAIR inhibited the HG‐induced pyroptosis and inflammatory response in cardiomyocytes. HOTAIR upregulated SIRT3 expression in H9C2 cells by targeting FUS. Moreover, SIRT3 upregulation suppressed HG‐mediated pyroptosis of cardiomyocytes. Notably, SIRT3 depletion reversed the inhibitory effect of HOTAIR on HG‐triggered pyroptosis in cardiomyocytes. Our research indicates that HOTAIR alleviates pyroptosis in diabetic cardiomyocytes through the FUS/SIRT3 axis, providing a potential marker for the diagnosis and treatment of DCM.